ANALISIS DESTINATION COMPETITIVENESS MODEL DALAM MENGEMBANGKAN SPORT TOURISM DI JATILUWIH: POTENSI INFRASTRUKTUR DAN PERSEPSI WISATAWAN - Nyoman Aril Raditya Tirta; Nathaniel Nathaniel; Pande Putu Aditya Baghaskara; Julius Andika Pratama Kabut; Dewa Putu Kiskenda Erwanda Putra (Kepariwisataan: Jurnal Ilmiah, 2026)
AbstractSport tourism has continued to grow alongside increasing tourist interest in physical activities and healthy lifestyles. Jatiluwih Area in Tabanan Regency possesses natural potential in the form of terraced rice fields and a rural landscape that supports the development of sport tourism, particularly running and cycling activities. This study aims to analyze the feasibility of developing sport tourism in Jatiluwih based on the perceptions of tourists and potential tourists. A qualitative descriptive approach was employed, with data collected through field observations, stakeholder interviews, and questionnaires as supporting data. The analysis was based on the Destination Competitiveness Model (DCM), which includes Core Resources, Supporting Factors, Destination Management and Demand Conditions. The results indicate that natural resources and supporting factors strongly support the development of sport tourism, while destination management and demand conditions are perceived as adequate but still require improvement. Overall, Jatiluwih is considered feasible to be developed as a nature based sport tourism destination with an emphasis on sustainable management.Keywords: Feasibility Study; Sport Tourism; Infrastructure; Tourist PerceptionsAbstrakSport tourism berkembang seiring meningkatnya minat wisatawan terhadap aktivitas olahraga dan gaya hidup sehat. Kawasan Jatiluwih di Kabupaten Tabanan memiliki potensi alam berupa lanskap persawahan terasering dan lingkungan pedesaan yang mendukung pengembangan sport tourism, khususnya aktivitas running dan cycling. Penelitian ini bertujuan untuk menganalisis kelayakan pengembangan sport tourism di Jatiluwih berdasarkan persepsi wisatawan dan calon wisatawan. Penelitian menggunakan pendekatan kualitatif deskriptif dengan pengumpulan data melalui observasi lapangan, wawancara pemangku kepentingan, serta kuesioner sebagai data pendukung. Analisis mengacu pada Destination Competitiveness Model (DCM) yang meliputi Core Resources, Supporting Factors, Destination Management, dan Demand Conditions. Hasil penelitian menunjukkan bahwa potensi sumber daya alam dan faktor pendukung dinilai sangat mendukung pengembangan sport tourism, sementara aspek pengelolaan destinasi dan kondisi permintaan dinilai cukup baik namun masih perlu ditingkatkan. Secara keseluruhan, Jatiluwih dinilai layak dikembangkan sebagai destinasi sport tourism berbasis alam dengan pengelolaan yang berkelanjutan.Kata Kunci: Studi Kelayakan; Sport Tourism; Infrastruktur; Persepsi Wisatawan